Interleukin-33 Induces Neutrophil Extracellular Trap (NET) Formation and Macrophage Necroptosis via Enhancing Oxidative Stress and Secretion of Proatherogenic Factors in Advanced Atherosclerosis - Manoj Kumar Tembhre; Mukesh Kumar Sriwastva; Milind Padmakar Hote; Shikha Srivastava; Priyanka Solanki; Shafaque Imran; Ramakrishnan Lakshmy; Alpana Sharma; Kailash Jaiswal; Ashish Datt Upadhyay (MDPI AG, 2022)
Interleukin-33 (IL-33) acts as an 'alarmin', and its role has been demonstrated in driving immune regulation and inflammation in many human diseases. However, the precise mechanism of action of IL-33 in regulating neutrophil and macrophage functioning is not defined in advanced atherosclerosis (aAT) patients. Further, the role of IL-33 in neutrophil extracellular trap (NET) formation in aAT and its consequent effect on macrophage function is not known. In the present study, we recruited n = 52 aAT patients and n = 52 control subjects. The neutrophils were isolated from both groups via ficoll/percoll-based density gradient centrifugation. The effect of IL-33 on the NET formation ability of the neutrophils was determined in both groups. Monocytes, isolated via a positive selection method, were used to differentiate them into macrophages from each of the study subjects and were challenged by IL-33-primed NETs, followed by the measurement of oxidative stress by calorimetric assay and the expression of the proinflammatory molecules by quantitative PCR (qPCR). Transcript and protein expression was determined by qPCR and immunofluorescence/ELISA, respectively. The increased expression of IL-33R (ST-2) was observed in the neutrophils, along with an increased serum concentration of IL-33 in aAT compared to the controls. IL-33 exacerbates NET formation via specifically upregulating CD16 expression in aAT. IL-33-primed NETs/neutrophils increased the cellular oxidative stress levels in the macrophages, leading to enhanced macrophage necroptosis and the release of atherogenic factors and matrix metalloproteinases (MMPs) in aAT compared to the controls. These findings suggested a pathogenic effect of the IL-33/ST-2 pathway in aAT patients by exacerbating NET formation and macrophage necroptosis, thereby facilitating the release of inflammatory factors and the release of MMPs that may be critical for the destabilization/rupture of atherosclerotic plaques in aAT. Targeting the IL-33/ST-2-NETs axis may be a promising therapeutic target for preventing plaque instability/rupture and its adverse complications in aAT.